THE RESULTS OF DEVELOPMENT OF AN INSTRUCTIONAL MODEL BASED ON CONNECTIVISM THEORY FOR PROMOTING INFORMATION LITERACY OF MATTAYOM SUKSA 1 STUDENTS - Pongprayoon, Patnaree; Thungnark, Nirut; Makemuengthong, Chomphunut (Chophayom Journal, 2017)
Abstract The purpose of this research was to study the results of development of an instructional model based on Connectivism theory of MattayomSuksa 1 students. The sample group in this study was the MattayomSuksa 1 students who took the information and communication course in the first semester of the academic year 2017 at PueaiNoiSuksa School. The research instruments used in the study were the plan of the instructional model based on Connectivism theory for promoting information literacy of MattayomSuksa 1 students and the information literacy test. The results of the research was that the students who studied by using the instructional model based on Connectivism theory had a progress in information literacy at 68% (E.I.= 0.68). The average score after learning by using the instructional model based on Connectivism theory was higher than the before learning’s score at the statistically significant level of .05. Keywords: Development of an instructional model; Connectivism theory; Information literacy